EXAMINING DEPRESSION IN ADOLESCENTS AND EXPLORING THE RELATIONSHIP BETWEEN ANTHROPOLOGY AND PUBLIC HEALTH: INTERVIEWING DR. STEVEN CORBETT - Masculine, Jenny (My University, 2022)
Depression is an invisible illness, one that does have a physical appearance like rashes or sores. Symptoms may include feeling sad, anxious, hopeless, pessimistic, worthless, guilty, helpless, irritable, and/or restless. In adolescents, depression is impactful and, if untreated, will carry into adulthood. There is an increase in prevalence of depression symptoms and diagnoses when compared to a decade ago. This is believed to be caused by the increased use of social media, which can be an avenue for bullying. Anthropology is a broad discipline that seeks to resolve issues and answer questions, especially when dealing with humanity. The discipline of public health is similar in that it also seeks to positively impact everyday lives. By taking a interdisciplinary approach, anthropology uses methodologies from public health, such as ways of describing health conditions through prevalence, incidence, morbidity, mortality, etc. In turn, public health utilizes concepts in anthropology like culture as a health factor, holism, critical perspectives, and qualitative analysis. The relationship between these two disciplines needs to continue. Leveraging my interest in both depression and anthropology, I pursued my applied practicum experience at the Kansas Department of Health and Environment (KDHE) in the Epidemiology and Public Health Informatics Bureau. In my applied practicum experience (APE), I explored the topic of depression by utilizing the 2019 Kansas Youth Risk Behavioral Surveillance System (YRBSS) Survey results. I was also able to explore the relationship between anthropology and public health by interviewing my preceptor, Dr. Steve Corbett to learn more about applied experiences of these dual disciplines. Key findings with the YRBSS showed that females, those who identified as Hispanic/Latino, and those who were multiracial were more likely to develop symptoms of depression than their counterparts.
Keywords: Kansas Department of Health and Environment; Public Health; Epidemiology; Depression; Anthropology